PENERAPAN PRIVATE ACCESS MENGGUNAKAN METODE PPTP DAN OVPN DI YAYASAN UMMU’L QURO DEPOK JAKARTA - Christo, Petrus; Mulyono, Hendro (Jurnal Informatika, 2022)
During the COVID-19 pandemic, the need for information technology is necessary and very important by various field such as institutions or individuals to increase productivity, both from the fields of work, health or learning. It's also affected the Ummu'l Quro Foundation Depok as an educational institution that requires communication and data exchange in carrying out its activities.This is a challenge for the Ummul Quro Foundation during this pandemic because of the location between kindergartens, elementary schools, junior high schools that are far apart, and so far the data exchange process is still using media such as flash drives, which is very ineffective, especially during the COVID19 pandemic.Therefore, requirement of bulid a network can accommodate the need for effective data exchangeusing the internet as a medium to carried out data over long distances. Using the VPN method as a solution for exchanging data online allows the security of data traffic communication on a computer network. This is very important, especially if the data is confidential. Data security needs to be implemented to prevent attacks or data theft. There are many ways to secure data on a computer network using a VPN, including the PPTP and OVPN methods to interconnect using a VPS as a backup for networks where there is no public IP available, both of which will be implemented using a mikrotik routerboard.